PENGARUH PENGGUNAAN METODE PEMBELAJARAN PQRST (PREVIEW, QUESTION, READ, SUMMARIZE AND TEST) TERHADAP KETERAMPILAN MEMBACA PEMAHAMAN SISWA KELAS V UPT SPF SDN 67 RAPPOKALLING MAKASSAR - Sulfasyah; Rosmini Madeamin; Muhammad Afif Al Ahyar (STKIP Subang, 2025)
This study aims to determine whether the PQRST learning method (Preview,Question, Read, Summary, and Test) has an effect on the reading comprehensionskills of fifth-grade students at UPT SPF SDN 67 Rappokalling, Makassar City.The research used a One Group Pretest-Posttest design with a sample of 30students. Data were collected through tests and documentation, then analyzedusing normality tests and hypothesis testing. The results showed that afterimplementing the PQRST method, the students' average score increased from 55in the pretest to 78.6 in the posttest. The t-test showed a significance value of lessthan 0.05, which means there was a significant effect of the method on students'reading comprehension skills. The PQRST method helps students read moreactively and systematically, making it easier for them to understand the text. Inconclusion, the PQRST method can improve the reading comprehension skills offifth-grade students at UPT SPF SDN 67 Rappokalling, Makassar City.